Chiro-optical response of a wafer scale metamaterial with ellipsoidal metal nanoparticles. (10th May 2021) - Ninawe, Akanksha; Suri, Priyanka; Xie, Zhuolin; Xu, Xianfan; Ghosh, Ambarish
Abstract: We report a large chiro-optical response from a nanostructured film of aperiodic dielectric helices decorated with ellipsoidal metal nanoparticles. The influence of the inherent fabrication variation on the chiro-optical response of the wafer-scalable nanostructured film is investigated using a computational model which closely mimics the material system. From the computational approach, we found that the chiro-optical signal is strongly dependent on the ellipticities of the metal nanoparticles and the developed computational model can account for all the variations caused by the fabrication process. We report the experimentally realized dissymmetry factor ∼1.6, which is the largest reported for wafer scalable chiro-plasmonic samples till now. The calculations incorporate strong multipolar contributions of the plasmonic interactions to the chiro-optical response from the tightly confined ellipsoidal nanoparticles, improving upon the previous studies carried in the coupled dipole approximation regime. Our analyzes confirm the large chiro-optical response in these films developed by a scalable and simple fabrication technique, indicating their applicability pertaining to manipulation of optical polarization, enantiomer selective identification and enhanced sensing and detection of chiral molecules.